2013
DOI: 10.1007/s11033-013-2780-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between obesity-related genes, FTO and MC4R, associated to an increase of breast cancer risk

Abstract: Breast cancer (BC) is a complex disease and obesity is a well-known risk factor for its development, especially after menopause. Several studies have shown Single Nucleotide Polymorphisms (SNPs) linked to overweight and obesity, such as: rs1121980 (T/C) and rs9939609 (A/T) in Fat Mass and Obesity Associated gene (FTO) and rs17782313 (T/C) in Melanocortin 4 Receptor gene (MC4R). Thus, we aimed to investigate the association between these obesity-related SNPs and BC risk. One hundred BC patients and 148 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…A number of studies have reported associations between FTO or MC4R variants and risk of various types of cancer [10, 11]; some of the associations were independent of obesity, but the mechanisms were unclear [11]. Our results are consistent with the few previous studies that reported null associations of FTO and MC4R with risk of colorectal cancer [35].…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies have reported associations between FTO or MC4R variants and risk of various types of cancer [10, 11]; some of the associations were independent of obesity, but the mechanisms were unclear [11]. Our results are consistent with the few previous studies that reported null associations of FTO and MC4R with risk of colorectal cancer [35].…”
Section: Discussionsupporting
confidence: 90%
“…Although there are various studies indicating the relationship between hormonal effects or the obesity gene and its direct effects, the mechanism has not yet been understood clearly (da Cunha et al, 2013). BMI was also found to be a risk factor in this study.…”
Section: Discussionmentioning
confidence: 45%
“…This variant has been associated with BMI, but the relation with etiological pathways for ER-negative breast cancer is unknown. However, when analyzing SNPs in 67 breast cancer susceptibility loci, Long et al [38] Finally, in a Brazilian population it was found that when FTO SNPs rs1121980 and rs9939609 were analyzed in combination with the presence of SNP rs17782313 in the melanocortin-4 receptor (MC4R), a 4.9-fold higher risk of developing breast cancer was observed [43]. Recently, Iles et al [44] found that other FTO SNPs present in an intron (e.g., intron 8) not associated with obesity may be associated with the risk of developing cancer (Table 1 summarizes all FTO SNPs positively associated with some type of cancer).…”
Section: Fto Polymorphisms and Cancermentioning
confidence: 99%